1979
DOI: 10.1002/bip.1979.360181009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metal ions on the hydrolysis of p‐nitrophenyl caproate by modified poly(ethylenimine)s

Abstract: SynopsisHydrolysis of nitrophenyl caproate by modified poly(ethy1enimine)s containing imidazole moieties is markedly enhanced in the presence of divalent metal ions. The order of effec-, with Cu increasing the rate about 20-fold. The acceleration by the metal ion is much greater in the presence of CH3COO-or C1-as counterions than in the presence of Clod-. Turnover experiments, in which moles of substrate cleaved were in substantial excess of moles of metal present, established the catalytic nature of the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Although fewer oligomeric polyiodide cations are known, their number is increasing.7 However, only one neutral moiety containing more than a single diodine molecule (bis(((triphenylphosphine sulfide-S)iodine)-/)iodine) appears to have been described. 8 We have now found that the family of neutral molecular compounds, with S as heteroatom in the donor and poly(diiodine) moieties as acceptors, is an extensive one, and we present crystal structure analyses of compounds with formulas • 2, •( 2 The present and earlier structural results suggest that two series of compounds are involved. In the first of these, diiodine chains of varying lengths are attached to sulfur-the examples considered here are • 2 and •( 2)2.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Although fewer oligomeric polyiodide cations are known, their number is increasing.7 However, only one neutral moiety containing more than a single diodine molecule (bis(((triphenylphosphine sulfide-S)iodine)-/)iodine) appears to have been described. 8 We have now found that the family of neutral molecular compounds, with S as heteroatom in the donor and poly(diiodine) moieties as acceptors, is an extensive one, and we present crystal structure analyses of compounds with formulas • 2, •( 2 The present and earlier structural results suggest that two series of compounds are involved. In the first of these, diiodine chains of varying lengths are attached to sulfur-the examples considered here are • 2 and •( 2)2.…”
mentioning
confidence: 74%
“…1978, 7, 697-702). 2(Dithizone)-7(I2) is triclinic (a = 13.312 (8) A, b = 20.637 (7) A, c = 9.746 (6) A, a = 101.8 (1)°, ß = 87.1 (1)°, y = 109. 4 (1)°, Z = 1, space group Pi; RF = 0.086) and has a centrosymmetric, branched twisted chain of iodine molecules held at its ends by strong sulfur-iodine interactions.…”
mentioning
confidence: 99%
“…PEI (MW 50 000−60 000, purchased from Aldrich) was purified by dialysis (cutoff MW 12 000). Laurylation of PEI was carried out with Lau bromide according to the procedure reported in the literature to obtain Lau 1 PEI, Lau 6 PEI, Lau 12 PEI, and Lau 18 PEI. The contents of Lau groups in Lau 1 PEI, Lau 6 PEI, Lau 12 PEI, and Lau 18 PEI were 1.2, 5.9, 12, and 18 residue mol %, respectively, as measured by NMR spectrometry.…”
Section: Methodsmentioning
confidence: 99%
“…The rate of p-nitrophenyl caproate hydrolysis by modified PEI, containing imidazole groups in the presence of metal ions, increased in the sequence Mn2+, Ni2+, Zn2+, Co2+, Cu2+ [92]. Among the selected metals, a copper complex was shown to be most effective, the maximum rate being achieved at a [imidazole]/[copper] ratio of 2.75.…”
Section: Menten Equation [64]mentioning
confidence: 99%
“…Polymers, with [q] = 0.30-0.56 dl/g, containing methyl sulfonyl groups have been synthesized by copolymerization of methyl-4-vinylphenyl sulfoxide with styrene [92]. These copolymers are soluble in toluene but are insoluble in water.…”
Section: Interfacial Catalysismentioning
confidence: 99%